2020
DOI: 10.1186/s12904-020-00556-7
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care utilization in oncology and hemato-oncology: a systematic review of cognitive barriers and facilitators from the perspective of healthcare professionals, adult patients, and their families

Abstract: Background: Despite the high potential to improve the quality of life of patients and families, palliative care services face significant obstacles to their use. In countries with high-resource health systems, the nonfinancial and nonstructural obstacles to palliative care services are particularly prominent. These are the cognitive barriers-knowledge and communication barriers-to the use of palliative care. To date no systematic review has given the deserved attention to the cognitive barriers and facilitator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 85 publications
2
58
0
11
Order By: Relevance
“…One might assume that these factors work as barriers to change, as well as to interprofessional collaborations. 16 Third, closely linked to the organizational challenges were a number of critical appraisals to colleagues in other professions and positions. In general, an insufficient level of communication and collaboration upward in the hierarchy appeared to be a challenge, which is also reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One might assume that these factors work as barriers to change, as well as to interprofessional collaborations. 16 Third, closely linked to the organizational challenges were a number of critical appraisals to colleagues in other professions and positions. In general, an insufficient level of communication and collaboration upward in the hierarchy appeared to be a challenge, which is also reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Knowledge of each other and available arenas to meet are two organizational-related factors that could be facilitators. 16,20 However, the current view on self and other HCPs seems to be a barrier that needs to be taken into account. For example, the oncologists neither experienced a great need for improved collaboration with palliative care services nor identified a need for earlier referrals of ''their'' patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, whether the decision-makers are the patients or their families can be a factor affecting the prognosis. Although previous studies have revealed the factors associated with difficulty and burden of the decision-making process, [ 22 , 23 ] it has been unclear to what extent the patient's self-decisions influenced the prognostic period. Information about how the survival period and palliative care would be affected by cancer treatment terminated by patients themselves, as compared to treatments terminated by the family, will lead to better decision-making support regarding the termination of cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Em tempos de pandemia, pode-se dizer que o adoecido limita sua relação com o mundo social um pouco mais do que já vivenciado. Em revisão sistemática sobre as repercussões do câncer entre profissionais de saúde, paciente e familiares, o elemento "comunicação" foi evidenciado por facilitar a translação de informações entre as pessoas e reduzir diversas barreiras criadas durante o processo de adoecimento 5 , como a barreira social.…”
Section: Introductionunclassified